SYNTHESIS OF 1,4-BIS [(1-HYDROXY-4-T-BUTYL-PHENYL) METHYL]PIPERAZINE AS ANTIOXIDANTS - Susy Yunita Prabawati (Molekul, 2016)
A study has been conducted to synthesize 1,4-bis [(1-hydroxy-4-t-butyl-phenyl)-methyl]piperazin using phenol derivate and investigate the capability of that compound, as an antioxidant. The synthesis was carried out through Mannich reaction using p-t-butylphenol, paraformaldehyde, and piperazine. The product was characterized by IR and 1H NMR spectroscopic. Testing of antioxidant activity was done with the immersion of DPPH (1,1-diphenyl-2 picrylhydrazyl) free radical method. The product was obtained as a white solid, with a point of 252,7-254,7 ºC and a yield of 65.76%. The test of antioxidant activity with DPPH method showed that 1,4-bis [(1-hydroxy-4-t-butyl-phenyl)-methyl]piperazin had the IC50 values was 0.84 nM. It means that the 1,4- bis[(1-hydroxy-4-t-butyl-phenyl )methyl]piperazine has potential as antioxidants.